Analisis Butir Soal Ujian Tengah Semester Pada Mata Pelajaran Pendidikan Agama Islam - Nurul Hidayah Siregar; Remiswal Remiswal; Khadijah Khadijah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2024)
This article aims to analyze the midterm exam questions conducted at Pertiwi 1 Padang Private High School in class XII, this is to see how far the questions play an important role in the evaluation process. Is it in accordance with the learning objectives to be achieved. So a question item analysis is needed to determine its suitability. The research method used is descriptive quantitative research which aims to describe events that occur using statistical data. data collection is done by documenting questions, answer keys and student answer sheets. The results of the research on the analysis of semester exam questions show that the validity found in the analysis of questions is 15 at the 75% level while the invalid ones are 5 at the 5% level. The reliability is 0.775. So it can be concluded that the data from the question items have high criteria. The difficulty index obtained is in the medium criteria as many as 12 questions at a percentage of 60%. The differential power of the analysis question is in the good category with a total of 8 questions at a percentage of 40%. Thus, every question made by educators is expected to have a good level of validity, reliability, difficulty index, and differentiation according to the category or criteria of the questions made